Integrating informal actors into the formal dairy industry in Kenya through training and certification - Omore, Amos O.; Baker, Derek (Alliance for a Green Revolution in Africa and International Livestock Research Institute, 2011)
This paper reviews current thinking on the role of informal agribusiness in pro-poor development, and reports on the example of a recent dairy development project (the Smallholder Dairy Project) in Kenya. The project featured collaborative and participatory research, along with training and certification in milk handling practices as a practical mechanism optimizing milk quality and addressing regulatory barriers. It also targeted and helped achieve policy change, which enabled wider piloting of the training and certification activities incorporating a business development service approach by national authorities. Substantial welfare gains were achieved, as demonstrated in a recent impact assessment reviewed in the current paper. Current extensions of the project are described, and subsequent work outlined. Coherence with received wisdom is discussed along with future research topics.